Star-forming regions towards stellar wind bubbles: the ring nebulae RCW 52 and RCW 78 - Cappa, Cristina Elisabeth (2011)
In a similar way to the expanding envelopes around H II regions, the dense shells surrounding stellar wind bubbles are potential sites for the formation of new stars. With the aim of investigating stellar formation activity in the molecular layers around the ring nebulae RCW 52 and RCW 78, we carried out observations of the continuum emission at 870 mic and 13 CO(2–1) line observations. The observational data were obtained with the Atacama Pathﬁnder Experiment (APEX), located in the north of Chile, in a region of 12 x 12´ in size towards RCW 52 and of 8 x 8´ in size towards RCW 78, using LABOCA bolometer array and APEX-1 SHFI instrument. The 13 CO(2–1) line observations obtained towards these ring nebulae revealed the dense and cold molecular clumps in which the protostar candidates are enshrouded and allowed us to analyze the kinematics of the clumps as well as to estimate their masses and densities. The optically thin continuum emission at 870 mic allowed us to ﬁnd the cold dust emission regions where the deeply embedded star forming sources are inmersed. Kinematical information conﬁrms the association of the YSOs to the dense molecular layer surrounding the stellar wind bubbles. Finally, we compare the stellar formation activity in these ring nebulae with previous studies of stellar wind bubbles and H II regions.